METHODS OF ORGANIZING THE TRAINING PROCESS OF ADOLESCENT TRIPLE JUMPERS AT THE INITIAL PREPARATION STAGE (Universal International Scientific Journal, 2026)
This article examines the methods of organizing the training process for young skiersin triple jump at the initial training stage (11-12 years old). The physiological characteristics ofadolescents, the use of G.V. Raschupkin's methodology for forming the basics of jumping technique,and the effectiveness of special exercise complexes were analyzed. The main focus is on forming therhythm of jumping and preparing the musculoskeletal system for specific loads
Keywords: triple jump; initial preparation; adolescents